2015
DOI: 10.5713/ajas.15.0478
|View full text |Cite
|
Sign up to set email alerts
|

Effect of <i>Bacillus subtilis</i> Natto on Meat Quality and Skatole Content in TOPIGS Pigs

Abstract: This study investigated the effect of Bacillus subtilis (B. subtilis) natto on meat quality and skatole in TOPIGS pigs. Sixty TOPIGS pigs were randomly assigned to 3 groups (including 5 pens per group, with 4 pigs in each pen) and fed with basic diet (control group), basic diet plus 0.1% B. subtilis natto (B group), and basic diet plus 0.1% B. subtilis natto plus 0.1% B. coagulans (BB group), respectively. All pigs were sacrificed at 100 kg. Growth performance, meat quality, serum parameters and oxidation stat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 25 publications
0
15
0
Order By: Relevance
“…In this study, the diet supplemented with FO decreased b* at 45 min and 48 hr, and increased a* at 48 hr, suggesting a regulatory role of FO on meat quality in pigs. These results likely because S. cerevisiae, B. subtilis, and L. plantarum had prebiotic effects on improving pork quality such as pH, hardness, stickiness, meat color, and fat content (Baowei, Guoqing, Qiaoli, & Bin, 2011;Kovacs-Zomborszky, Feher, & Soos, 1997;Sheng et al, 2016;Suo et al, 2012).Therefore, FO seems to serve as a functional feed to improve pork quality by regulating meat color such as b* and a* values, especially at 48 hr postmortem. Previous research declared that a* values were correlated to pigment content and redox state, but b* was only related to redox state rather than pigment content (Lindahl, Lundstrom, & Tornberg, 2001;Mancini & Hunt, 2005), which accorded to results in this study.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, the diet supplemented with FO decreased b* at 45 min and 48 hr, and increased a* at 48 hr, suggesting a regulatory role of FO on meat quality in pigs. These results likely because S. cerevisiae, B. subtilis, and L. plantarum had prebiotic effects on improving pork quality such as pH, hardness, stickiness, meat color, and fat content (Baowei, Guoqing, Qiaoli, & Bin, 2011;Kovacs-Zomborszky, Feher, & Soos, 1997;Sheng et al, 2016;Suo et al, 2012).Therefore, FO seems to serve as a functional feed to improve pork quality by regulating meat color such as b* and a* values, especially at 48 hr postmortem. Previous research declared that a* values were correlated to pigment content and redox state, but b* was only related to redox state rather than pigment content (Lindahl, Lundstrom, & Tornberg, 2001;Mancini & Hunt, 2005), which accorded to results in this study.…”
Section: Discussionmentioning
confidence: 99%
“…Currently, several studies have confirmed that B. subtilis has great application value in animal husbandry. It was reported that pig feed with B. subtilis natto could significantly improve meat quality and flavor (Sheng et al, 2016). Liu et al (2017) also demonstrated that dietary corn bran fermented by B. subtilis MA139 could decrease gut cellulolytic bacteria and microbiota diversity in finishing pigs.…”
Section: Introductionmentioning
confidence: 99%
“…as probiotics can also affect the production of malodorous substances such as skatole. Skatole is a malodorous compound in meat and fecal that causes an off-flavor, so called "boar taint" [32]. Sheng et al [33] demonstrated that dietary B. subtilis natto and B. coagulans supplementation decreased the skatole content of meat and feces.…”
Section: Archives Of Animal and Poultry Sciences (Aaps)mentioning
confidence: 99%
“…Davis et al [39] also reported that two probiotic Bacillus strains (B. licheniformis and B. subtilis) were ineffective in improving the growth performance in growing and finishing pigs, when they were supplied in feed during test period. Moreover, Sheng et al [32] also found that the dietary supplementation of two probiotic complex (B. subtilis natto and B. coagulans) did not show a remarkable improvement of growth performance in growing pigs, but indicate dramatical effects in terms of meat quality, antioxidant function, and the skatole content of meat. The effects of Bacillus-based probiotics are influenced by a variety of factors, (e.g., age of the pigs, diet composition, differences in strains of bacteria, dosage levels, and breeding environment) [41].…”
Section: Growth Performance In Swinementioning
confidence: 99%